Needs assessment - Royse, David D. (David Daniel) (New York ; Oxford : Oxford University Press, 2009)
This text features discussions on emerging technologies in the field of needs assessment as well as abundant social work case examples. It covers one of the most essential kinds of research for social work management.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social case work -- Methdology; Social case work -- Evaluation; Needs assessment